Positive electrode active material particle and preparation method thereof, positive electrode plate, battery monomer, battery and electric device

By covering MQ silicone on the surface of the positive electrode active material particles to form a polymer cladding layer, the problem of high moisture content of the positive electrode active material is solved, the stability and life of the battery are improved, and the balance between hydrophobicity and interface stability is achieved.

CN120261504APending Publication Date: 2025-07-04CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410008960.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-03
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

In the prior art, the moisture content improvement effect of the cathode active material still needs to be improved, affecting the stability and life of the battery.

Method used

The positive electrode active material particles are coated with a polymer cladding layer containing MQ silicone resin to form a balance between hydrophobicity and interface stability, reduce moisture infiltration, and improve material stability and interface compatibility.

Benefits of technology

The moisture content of the positive electrode active material particles is reduced, the stability and life of the battery is improved, and the interface compatibility and electrochemical performance are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120261504A_ABST
    Figure CN120261504A_ABST
Patent Text Reader

Abstract

The invention discloses a positive active material particle and a preparation method thereof, a positive pole piece, a battery monomer, a battery and an electric device, the positive active material particle has a polymer coating layer, and the polymer coating layer contains MQ silicon resin. The positive electrode active material particle provided by the embodiment of the invention has the polymer coating layer containing the MQ silicon resin, so that the water content of the positive electrode active material particle is relatively low, the stability and interface stability of the positive electrode active material particle are improved, and the service life of a battery can be prolonged; the invention also aims at a positive pole piece containing the positive active material particles, and the positive pole piece at least has the beneficial effects of the positive active material particles. According to the battery monomer, the battery and the power utilization device, the beneficial effects of the positive pole piece can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the technical field of batteries, and particularly relates to a positive electrode active material particle, a preparation method thereof, a positive electrode sheet, a battery cell, a battery, and an electrical device. Background Art

[0002] In recent years, with the wide application of battery cells represented by lithium-ion batteries, their performance has received increasing attention. And the requirements for the water content of the positive electrode active material are getting higher and higher.

[0003] In related technologies, the positive electrode active material is modified. The modification methods include directly doping a hydrophobic substance, surface hydrophobic modification, or coating a hydrophobic substance on the surface of the positive electrode active material, etc.; however, the improvement effect on the water content of the positive electrode active material still needs to be further improved. Summary of the Invention

[0004] The purpose of this application is to provide a positive electrode active material particle, a preparation method thereof, a positive electrode sheet, a battery cell, a battery, and an electrical device. The positive electrode active material particle provided by the embodiments of this application has a polymer coating layer containing MQ silicone resin, so that the water content of the positive electrode active material particle is relatively low; during the charge and discharge process of the battery, the stability of the positive electrode active material particle and the interface stability are improved, thereby being able to improve the service life of the battery; this application also aims at a positive electrode sheet containing the positive electrode active material particle, which at least has the beneficial effects of the positive electrode active material particle. This application provides a battery cell, a battery, and an electrical device that can achieve the beneficial effects of the positive electrode sheet.

[0005] In a first aspect, an embodiment of this application provides a positive electrode active material particle, and the positive electrode active material particle has a polymer coating layer, wherein the polymer coating layer contains MQ silicone resin.

[0006] According to the embodiments of this application, as the main component of the polymer coating layer, MQ silicone resin has a hydrophobic effect. MQ silicone resin is a kind of organosilicon resin with a relatively unique three-dimensional spherical structure, which can include M structural units with monofunctionality, that is, organosiloxane closed chain segments R3SiO 1 / 2 and polysiloxane formed with Q structural units with tetrafunctionality. Generally, it is considered that MQ silicone resin is a spherical body with a tightly structured double layer, where the core of the sphere is connected by Si-O chains and has a relatively high density, forming a cage-like SiO2, and the shell of the sphere is a layer with a relatively low density of R3SiO 1 / 2 layer.

[0007] Compared with other organic polymers, the inner cage-like SiO2 structure of MQ silicone resin endows the material with excellent stability, chemical corrosion resistance and excellent hydrophobicity. The organic groups on the outer layer of MQ silicone resin can endow the material with good interfacial compatibility. Compared with pure inorganic materials, it is easier to form a film coating on the positive active material particles and firmly bond them. Compared with organosilane modification or silane coupling agent modification, MQ silicone resin has a more complete coating on the positive active material particles and fewer interfacial defects. And the coating layer containing MQ silicone resin, due to its three-dimensional spherical structure, does not hinder the migration of lithium ions compared with other polymers, significantly reducing the deterioration of electrochemical performance.

[0008] Generally speaking, the positive active material particles of the embodiments of the present application have a polymer coating layer, which can achieve a balance between hydrophobicity and interfacial stability compared with the traditional pure inorganic or organic materials used, and further improve the hydrophobic performance of the positive active material particles on the premise of ensuring good interfacial adhesion effect and electrochemical performance.

[0009] According to the embodiments of the present application, the positive active material particles have a polymer coating layer, which can prevent moisture from other sources such as air from infiltrating into the positive active material particles, thereby reducing the chance of contact between the positive active material particles and moisture, and keeping the water content of the positive active material particles at a low level.

[0010] During the use of the battery containing the positive active material particles, the moisture present in the electrolyte has a certain impact on the performance of the positive active material particles. The positive active material particles having a polymer coating layer can reduce the contact between the positive active material particles and the electrolyte, reduce the positive active material particles from obtaining moisture in the electrolyte, reduce the occurrence of side reactions, and improve the stability of the positive active material particles. Further, the organic groups on the outer layer of MQ silicone resin can endow the material with good interfacial compatibility, which is beneficial to the desolvation of active ions, and MQ silicone resin does not significantly hinder the active ions from reaching the transmission; the inner cage-like SiO2 structure of MQ silicone resin endows the material with excellent stability, chemical corrosion resistance and excellent hydrophobicity, which can improve the stability of the positive active material particles, all of which contribute to extending the cycle life of the battery.

[0011] In some optional embodiments, MQ silicone resin includes the structural unit represented by M and the structural unit represented by Q:

[0012]

[0013] Among them, the O in the structural unit represented by M and the structural unit represented by Q 1 / 2It means that the oxygen atom is shared with another structural unit. R1, R2, and R3 each independently represent hydrogen, C1-C5 alkenyl, haloalkyl, C3-C7 alkenoate group, phenyl, an alkyl group containing 1-6 carbon atoms which is unsubstituted or substituted by a substituent, or an alkylene oxide containing 2-4 carbon atoms; the substituent includes any one of fluorine and chlorine elements.

[0014] According to the embodiments of the present application, for the MQ silicone resin having the above structural unit, a polymer coating layer is formed. The organic groups on the outer layer of the MQ silicone resin can endow the material with good interfacial compatibility, and the groups inside the MQ silicone resin have good binding properties with the matrix inside the positive electrode active material particles, so that the MQ silicone resin is tightly and firmly bonded to the surface of the positive electrode active material particles. And some organic groups such as methyl groups, fluorine-containing groups, and higher alkyl groups, etc., which are hydrophobic groups, can further improve the hydrophobic performance of the positive electrode active material particles on the basis of the inner-layer cage-like SiO2 structure.

[0015] The above types of hydrophobic functional groups can reduce the moisture in the air and electrolyte adsorbed by the positive electrode active material particles containing the MQ silicone resin, so that it has a lower water content during storage and use.

[0016] In some optional embodiments, the weight-average molecular weight of the MQ silicone resin is 4000-20000, and can be optionally 5000-10000.

[0017] According to the embodiments of the present application, when the weight-average molecular weight of the MQ silicone resin is within the above range, it can have an appropriate amount of molecular chain segments, which can increase the hydrophobicity of the polymer; it can also increase the bonding strength with other components in the positive electrode active material film layer, which helps to reduce the probability of the positive electrode active material particles falling off during the battery cycling process, thereby improving the stability and cycle life of the battery.

[0018] The weight-average molecular weight of the MQ silicone resin within the above range is beneficial to the MQ silicone resin having a certain fluidity and cohesive strength on the surface of the positive electrode active material particles. It alleviates the situation that when the weight-average molecular weight of the MQ silicone resin is too high, the MQ silicone resin is not easy to disperse and cannot form a uniform hydrophobic coating layer; it also alleviates the adverse effects such as low cohesive strength and poor viscosity of the MQ silicone resin when the weight-average molecular weight of the MQ silicone resin is too low.

[0019] In some optional embodiments, the glass transition temperature of the MQ silicone resin is 40-200 °C. According to the embodiments of the present application, when the glass transition temperature of the MQ silicone resin is within the above range, it can have an appropriate glass transition temperature; it can increase the bonding strength with other components in the positive electrode active material film layer, which helps to reduce the probability of the positive electrode active material particles falling off during the battery cycling process, thereby improving the stability and cycle life of the battery.

[0020] In some alternative embodiments, the molar ratio of the structural unit represented by M to the structural unit represented by Q in the MQ silicone resin is (0.5 to 1.2):1, optionally (0.7 to 0.9):1, and optionally 0.75:1.

[0021] According to the embodiments of the present application, when the molar ratio of the structural unit represented by M to the structural unit represented by Q is within the above range, it is beneficial to the compatibility and fluidity of the MQ silicone resin. Within the above range, the larger the molar ratio, the more the content of the organic M structural unit in the silicone resin, and the better the compatibility and fluidity of the molecules. The smaller the molar ratio, the more the content of the organic Q structure in the silicone resin, and the better the strength and stability of the molecules. When the molar ratio of the MQ silicone resin in the polymer coating layer exceeds the above range, the MQ silicone resin has low strength and is easy to flow, and is easy to form a film. However, too many organic groups are likely to accumulate and hinder the migration of active ions, especially the migration of lithium ions, affecting the kinetics of lithium batteries. When the molar ratio of the MQ silicone resin in the polymer coating layer is less than the above range, the polymer has poor compatibility, is not easy to form a film, and the polymer coating layer is easy to fall off, and the hydrophobic effect is poor.

[0022] In some alternative embodiments, R1, R2, and R3 each independently represent any one of hydrogen, C1-C5 alkenyl, haloalkyl, C3-C7 alkenoate group, and phenyl; optionally, the C3-C7 alkenoate includes acrylate group; optionally, the acrylate group includes any one of methyl acrylate group, ethyl acrylate group, methyl 2-methylacrylate group, and ethyl 2-methylacrylate group; optionally, the haloalkyl includes trifluoromethyl and chloromethyl. According to the embodiments of the present application, some groups in R1, R2, and R3 have hydrophobic groups such as methyl group, fluorine-containing group, and high alkyl group, which can further improve the hydrophobic performance of the positive electrode active material particles on the basis of the inner layer cage-like SiO2 structure.

[0023] In some alternative embodiments, based on the total mass of the positive electrode active material particles, the positive electrode active material particles include 0.01% to 5% by mass of the MQ silicone resin.

[0024] According to the embodiments of the present application, the positive electrode active material particles including the MQ silicone resin in the above content are beneficial to forming a uniform coating layer with a suitable thickness, effectively improving the hydrophobic performance of the positive electrode active material particles, and preventing moisture from entering the inside of the positive electrode active material particles to reduce the water content of the positive electrode active material particles. Moreover, due to the double-layer spherical structure of the MQ silicone resin, the uniform polymer coating film will not significantly limit the migration of lithium ions, avoiding significantly reducing the capacity retention rate of the battery and affecting the battery impedance.

[0025] When the content of MQ silicone resin in the positive electrode active material particles is lower than the above range, a complete coating layer may not be formed, resulting in a poor coating effect and reducing its hydrophobic performance. On the other hand, the incomplete coating or the existence of defects may cause the MQ silicone resin to not be tightly bonded to the matrix inside the positive electrode active material particles, and may easily lead to the detachment of the MQ silicone resin under the action of external forces or other factors, and even cause the coating layer to fail to function. On the contrary, when the content of MQ silicone resin in the positive electrode active material particles exceeds the above range, the coating layer will be too thick, which may hinder the transport of lithium ions in the lithium battery, may affect the migration rate of lithium ions, and thus affect the battery kinetics.

[0026] According to the embodiments of the present application, when the MQ silicone resin in the positive electrode active material particles is within the above suitable range, while taking into account the battery kinetics performance, the contact between the positive electrode active material particles and the electrolyte can be reduced, the moisture in the electrolyte can be reduced, the occurrence of side reactions can be reduced, and the stability and cycle life of the positive electrode active material particles can be improved. Compared with the uncoated positive electrode active material particles, the positive electrode active material particles with the above coating layer have better surface elasticity, which can further improve the adhesion and cohesion of the positive electrode sheet. Therefore, by further controlling the coating amount, better battery cycle performance and low anti-swelling performance can be obtained.

[0027] In some alternative embodiments, the positive electrode active material particles include a binder; optionally, based on the total mass of the positive electrode active material particles, the positive electrode active material particles include 0-2.5% binder.

[0028] According to the embodiments of the present application, the binder can promote the formation of a complete and uniform polymer coating layer by MQ silicone resin, and improve the integrity and uniformity of the coating of the positive electrode active material particles.

[0029] In some alternative embodiments, the mass ratio of the binder to the MQ silicone resin is (0.01-0.5):1, and can be optionally (0.1-0.25):1.

[0030] According to the embodiments of the present application, when the mass ratio of the binder to the MQ silicone resin is within the above range, the binder can promote the formation of a complete and uniform polymer coating layer by MQ silicone resin, and improve the integrity and uniformity of the coating of the positive electrode active material particles. When the mass ratio of the binder to the MQ silicone resin is lower than the above range, the formed polymer coating layer is uneven and easy to fall off, and cannot achieve a good hydrophobic effect; on the contrary, when the mass ratio of the binder to the MQ silicone resin is higher than the above range, the mass ratio of organic components such as the binder in the coating layer is higher than the above range, which not only cannot prevent moisture from entering the inside of the positive electrode active material particles, but also affects the kinetic process of the lithium battery.

[0031] In some alternative embodiments, the binder includes one or more of acrylic binders, polyurethane binders, silicone binders, polyvinylidene fluoride binders, and epoxy resin binders.

[0032] According to the embodiments of the present application, binders of the above types have good compatibility with some groups in MQ silicone resin or have structural characteristics similar to those of MQ silicone resin. Therefore, they can have a good promoting effect on MQ silicone resin, promote the formation of a complete and uniform polymer coating layer on MQ silicone resin, and improve the integrity and uniformity of the coating of the positive electrode active material particles.

[0033] In some alternative embodiments, the average thickness of the polymer coating layer is 100 nm to 200 nm.

[0034] According to the embodiments of the present application, when the amount of the polymer coating layer is controlled within a certain range, on the basis of taking into account the battery kinetic performance, the contact between the positive electrode active material particles and the electrolyte can be reduced, the moisture in the electrolyte can be reduced, the occurrence of side reactions can be lowered, and the stability and cycle life of the positive electrode active material particles can be improved. Compared with the uncoated positive electrode active material particles, the positive electrode active material particles with the above polymer coating layer have better surface elasticity, which can further improve the adhesion and cohesion of the positive electrode sheet. Therefore, by further controlling the polymer coating amount, better battery cycle performance and low anti-swelling performance can also be obtained.

[0035] The average thickness of the coating layer can be calculated by sampling and detecting the average thickness of the coating layer in the cross-section of the positive electrode active material particles.

[0036] In some alternative embodiments, the positive electrode active material particles have a core-shell structure in which the coating layer coats the positive electrode active material core.

[0037] According to the embodiments of the present application, the positive electrode active material particles with a core-shell structure have a relatively complete and uniform coating, which can prevent moisture from penetrating into the interior of the positive electrode active material particles, reduce the overall moisture content of the positive electrode active material particles, and thus reduce the chance of contact between the positive electrode active material particles and moisture. The shell contains a polymer, which reduces the contact between the positive electrode active material particles and the electrolyte, can reduce the moisture in the electrolyte, lower the occurrence of side reactions, and improve the stability of the positive electrode active material particles.

[0038] In some alternative embodiments, the positive electrode active material particles include one or more of layered metal oxide materials, olivine-type positive electrode materials, and spinel-type materials; optionally, the olivine-type positive electrode material includes lithium iron phosphate material; optionally, the positive electrode active material particles include one or more of lithium nickel cobalt manganese oxide materials and lithium nickel cobalt aluminum oxide materials.

[0039] According to the embodiments of the present application, the common cathode active material particles include the above types. The specific polymer coating layer on the surface of the cathode active material particles of the above types can reduce the overall moisture content of the cathode active material particles, reduce the occurrence of side reactions, and improve the stability of the cathode active material particles.

[0040] In some alternative embodiments, the average particle size Dv50 of the cathode active material particles is 0.52 μm to 4.1 μm, and may be 0.9 μm to 1.9 μm.

[0041] According to the embodiments of the present application, the cathode active material particles with the above average particle size are beneficial to the electrochemical performance in the cathode electrode sheet, and also have a relatively high specific surface area to increase the capacity of the battery, improve the energy density of the battery, and enable it to store more electrical energy. The cathode active material particles with the above average particle size contribute to the ion and electron transport between the electrolyte and the cathode active material particles, and can improve the charge and discharge speed of the battery. The cathode active material particles with the above average particle size can reduce the stress of the electrode, reduce the volume expansion and contraction of the material, thereby reducing the loss of the battery during the cyclic charge and discharge process and extending the life of the battery.

[0042] In some alternative embodiments, the specific surface area of the cathode active material particles is 7 m 2 / g to 18 m 2 / g, and may be 10 m 2 / g to 15 m 2 / g.

[0043] According to the embodiments of the present application, the specific surface area of the cathode active material particles within the above range means that there are more active sites available for electrochemical reactions, so the capacity of the battery is larger, and the energy density of the battery can also be improved; the above relatively large specific surface area has more active surfaces that can accelerate the transport of ions and electrons in the electrolyte, thereby reducing the charging and discharging time and contributing to improving the charging and discharging speed of the battery. The above relatively large specific surface area is usually accompanied by a more uniform utilization of the electrode material, reducing the material loss and contributing to extending the life of the battery.

[0044] In a second aspect, the embodiments of the present application provide a method for preparing cathode active material particles with a polymer coating layer, including:

[0045] Providing a mixture containing cathode active material raw material particles, MQ silicone resin, and a solvent;

[0046] Drying the mixture to form a polymer coating layer covering the cathode active material raw material particles.

[0047] According to an embodiment of the present application, MQ silicone resin, as the main component of the coating layer of the positive electrode active material particles, has a hydrophobic effect. MQ silicone resin is a silicone resin with a relatively unique three-dimensional spherical structure, which may include an M structure with monofunctionality, and a polysiloxane formed by an organosiloxane closed chain segment R3SiO 1 / 2 and a Q structure with tetrafunctionality. Generally, MQ silicone resin is considered to be a spherical body with a tightly packed double-layer structure, in which the core of the sphere is connected by Si—O chains and has a relatively high density, forming a cage-like SiO2, and the shell of the sphere is a layer with a relatively low density of R3SiO 1 / 2 layer.

[0048] Compared with other organic polymers, the cage-like SiO2 structure in the inner layer of MQ silicone resin endows the material with excellent stability, chemical corrosion resistance and excellent hydrophobicity. The organic groups in the outer layer of MQ silicone resin can endow the material with good interfacial compatibility. Compared with pure inorganic materials, it is easier to form a film coating on the positive electrode active material particles and firmly bond them. Compared with organosilane modification or silane coupling agent modification, MQ silicone resin forms a more complete coating on the positive electrode active material particles and has fewer interfacial defects. And the coating layer containing MQ silicone resin is composed of a three-dimensional spherical structure stacked together, which does not hinder the migration of lithium ions and reduces the deterioration effect on the electrochemical performance. Generally speaking, the positive electrode active material particles in the embodiment of the present application have a polymer coating layer, which can achieve a balance between hydrophobicity and interfacial stability compared with the traditional pure inorganic or organic materials used, and further improve the hydrophobic performance of the positive electrode active material particles on the premise of ensuring good interfacial adhesion effect and electrochemical performance.

[0049] According to an embodiment of the present application, the positive electrode active material particles have a polymer coating layer, which can prevent moisture from other sources such as air from infiltrating into the positive electrode active material particles, thereby reducing the chance of contact between the positive electrode active material particles and moisture, and keeping the water content of the positive electrode active material particles at a relatively low level.

[0050] When the positive electrode active material particles are used in a battery, the moisture present in the electrolyte has a certain influence on the performance of the positive electrode active material particles. The positive electrode active material particles having a polymer coating layer can reduce the contact between the positive electrode active material particles and the electrolyte, thereby reducing the amount of moisture obtained by the positive electrode active material particles from the electrolyte, reducing the occurrence of side reactions, and improving the stability of the positive electrode active material particles. Further, the organic groups in the outer layer of MQ silicone resin can endow the material with good interfacial compatibility, which is beneficial to the desolvation of active ions, and MQ silicone resin does not hinder the active ions from reaching and transporting, which is beneficial to the charge and discharge performance of the battery; the cage-like SiO2 structure in the inner layer of MQ silicone resin endows the material with excellent stability, chemical corrosion resistance and excellent hydrophobicity, which can improve the stability of the positive electrode active material particles, and all contribute to extending the life and cycle life of the battery or energy storage system.

[0051] In some alternative embodiments, the mass ratio of the MQ silicone resin to the raw material particles of the positive electrode active material is (0.01-5):100.

[0052] According to the embodiments of the present application, when the mass ratio of the MQ silicone resin to the raw material particles of the positive electrode active material is within the above range, it is beneficial to form a uniform polymer coating layer with a suitable thickness, effectively improving the hydrophobic property of the positive electrode active material particles and preventing moisture from entering the interior of the positive electrode active material particles to reduce the water content of the positive electrode active material particles. Moreover, due to the double-layer spherical structure of the MQ silicone resin, the uniform thin film of the polymer coating layer will not significantly limit the migration of lithium ions, avoiding the reduction of the battery capacity retention rate and the influence on the battery impedance.

[0053] In a third aspect, the embodiments of the present application provide a positive electrode plate, including a positive electrode current collector and a positive electrode active material film layer disposed on at least one side of the positive electrode current collector, and the positive electrode active material film layer includes the positive electrode active material particles of the first aspect or the positive electrode active material particles prepared by the preparation method of the second aspect.

[0054] According to the embodiments of the present application, the positive electrode plate containing the above positive electrode active material particles is beneficial to form a uniform positive electrode active material film layer. The water content of the positive electrode active material particles therein is relatively low. When they exist in the positive electrode active material film layer, it can improve the stability of the positive electrode plate during the use of the battery, and contribute to extending the service life of the battery or energy storage system. The polymer on the surface of the positive electrode active material particles can reduce the contact between the positive electrode active material particles and the electrolyte, reduce the water obtained by the positive electrode active material particles from the electrolyte, and reduce the occurrence of side reactions, which is beneficial to the cycle performance.

[0055] In a fourth aspect, the embodiments of the present application provide a battery cell, including the positive electrode plate of the third aspect. The battery cell of the embodiments of the present application contains the above positive electrode plate, which helps to extend the service life and cycle performance of the battery.

[0056] In a fifth aspect, the embodiments of the present application provide a battery, including the battery cell of the fourth aspect.

[0057] In a sixth aspect, the embodiments of the present application provide an electrical device, including the battery of the fifth aspect.

[0058] The positive electrode active material particles of the embodiments of the present application have a polymer coating layer, which improves the stability of the positive electrode active material particles. The MQ silicone resin can reduce the contact between the positive electrode active material particles and the electrolyte, reduce the water obtained by the positive electrode active material particles from the electrolyte, and reduce the occurrence of side reactions, which is beneficial to the cycle performance. The positive electrode plate, battery cell and electrical device containing the positive electrode active material have at least the above advantages. Description of the Drawings

[0059] To more clearly illustrate the technical solutions of the embodiments of the present application, the accompanying drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present application. For those of ordinary skill in the art, without creative efforts, other drawings can be obtained based on the drawings.

[0060] Figure 1 A schematic diagram showing an embodiment of the battery cell of the present application is shown.

[0061] Figure 2 Shows Figure 1 An exploded schematic diagram of the battery cell shown.

[0062] Figure 3 A schematic diagram showing an embodiment of an electrical device including the battery cell of the present application as a power source is shown.

[0063] Figure 4 Micrographs and elemental distribution maps of the positive electrode active material particles prepared in Example 1 and Comparative Example 1 of the present application are shown.

[0064] Figure 5 A graph showing the change in moisture content of the positive electrode active material particles prepared in Example 1 and Comparative Example 1 of the present application during storage is shown.

[0065] In the accompanying drawings, the drawings are not necessarily drawn to actual scale. Detailed implementation manners

[0066] Hereinafter, embodiments of the electrode assembly, its preparation method, battery cell, battery module, battery pack, and electrical device of the present application will be specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually identical structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the accompanying drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter recited in the claims.

[0067] The "ranges" disclosed in this application are defined in the form of a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The ranges defined in this way can include or exclude the end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60 - 120 and 80 - 110 are listed for a specific parameter, ranges of 60 - 110 and 80 - 120 are also contemplated. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4, and 5 are listed, then the following ranges are all contemplated: 1 - 3, 1 - 4, 1 - 5, 2 - 3, 2 - 4, and 2 - 5. In this application, unless otherwise specified, the numerical range "a - b" represents an abbreviated representation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0 - 5" represents that all real numbers between "0 - 5" are fully listed herein, and "0 - 5" is just an abbreviated representation of these numerical combinations. Additionally, when stating that a certain parameter is an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0068] If there is no special instruction, all embodiments and alternative embodiments of this application can be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.

[0069] If there is no special instruction, all technical features and alternative technical features of this application can be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.

[0070] If there is no special instruction, all steps of this application can be carried out sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method can include steps (a) and (b) carried out sequentially, or can also include steps (b) and (a) carried out sequentially. For example, when it is mentioned that the method may further include step (c), it means that step (c) can be added to the method in any order. For example, the method can include steps (a), (b), and (c), or can also include steps (a), (c), and (b), or can also include steps (c), (a), and (b), etc.

[0071] If there is no special instruction, the "including" and "comprising" mentioned in this application mean open-ended, and can also be closed-ended. For example, the "including" and "comprising" can mean that other components not listed can also be included or comprised, or can also mean that only the listed components are included or comprised.

[0072] Unless otherwise specified, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0073] Unless otherwise specified, in this application, the terms "connected" and "coupled" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be directly connected or indirectly connected through an intermediate medium, and it can be the communication inside two components. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0074] Unless otherwise specified, in this application, the term "attached" refers to connection by means such as adhesion or coating.

[0075] Unless otherwise specified, in this application, the terms "first", "second", "third", "fourth", etc. are used to distinguish different objects, rather than to describe a specific order or primary-secondary relationship.

[0076] Unless otherwise specified, in this application, the term "active ion" refers to an ion that can intercalate and deintercalate between the positive and negative electrodes of a battery cell, including but not limited to lithium ions, sodium ions, etc.

[0077] In this application, "a plurality of" means two or more (including two). "A variety of" and "several" in this application mean two or more (including two).

[0078] In this application, the battery cell may include a lithium-ion battery, a sodium-ion battery, etc., and the embodiments of this application do not limit this. The battery cell can be an aqueous battery or an oil-based battery, and the embodiments of this application do not limit this either. The battery cell can be in the shape of a flat body, a cuboid, or other shapes, and the embodiments of this application do not limit this either.

[0079] The battery cell is also called a rechargeable battery or a storage battery, which refers to a battery that can activate the active material through charging after discharging. Usually, the battery cell includes an electrode assembly and an electrolyte, and the electrode assembly includes a positive electrode plate, a negative electrode plate, and a separator.

[0080] The main raw materials of the battery include cathode active material particles, anode materials, separators, electrolytes, etc. During the charging and discharging process of the battery, electrochemical oxidation / reduction reactions occur in the cathode active material particles, and active ions represented by lithium ions are repeatedly intercalated into and deintercalated from the cathode active material particles. The cathode active material particles mainly include layered structure materials, spinel structure materials, and olivine structure materials.

[0081] To ensure good electrochemical performance, strict requirements are imposed on the performance of the cathode active material particles. One of the more important points is that the cathode active material particles have good chemical stability and do not undergo side reactions with electrolytes, etc. During the preparation and storage of the cathode active material particles, they are often exposed to a humid environment, resulting in a certain amount of water on the surface. The presence of water reduces the chemical stability of the cathode active material particles and their side reactions with electrolytes, etc.

[0082] When the cathode active material absorbs a certain amount of moisture during storage for preparing the slurry, it will make the slurry present a jelly state, making it difficult to coat the slurry. And the presence of moisture during the subsequent use of the cathode active material will also cause side reactions, resulting in a sharp decline in battery performance. Therefore, drying the cathode active material before use not only increases the complexity of the process but also raises the manufacturing cost of the battery.

[0083] Currently, the main methods to solve the above problems are to modify the cathode active material. The modification methods include directly doping hydrophobic substances, surface hydrophobic modification, or coating hydrophobic substances on the surface of the cathode active material, etc. However, the water absorption of the cathode active material prepared by the existing optimization and modification methods is still relatively large. Without drying treatment, the cathode active material cannot well meet the usage requirements of the battery. Therefore, there is an urgent need to develop a hydrophobic cathode active material to solve the problems of slurry coating of the cathode active material and storage of the subsequent cathode electrode sheet.

[0084] In view of this, the present application provides a cathode active material particle coated with a polymer coating layer to solve the above problems.

[0085] Cathode active material particles

[0086] In the first aspect, an embodiment of the present application provides a cathode active material particle, and the cathode active material particle has a polymer coating layer, wherein the polymer coating layer contains MQ silicone resin.

[0087] According to the embodiment of the present application, MQ silicone resin, as the main component of the polymer coating layer, has a hydrophobic effect. MQ silicone resin is a unique organosilicon resin with a three-dimensional spherical structure, which can include M structural units with monofunctionality, that is, organosiloxane closed chain segments R3SiO 1 / 2Polysiloxanes formed with Q structural units having tetrafunctionality. It is generally believed that MQ silicone resin is a spherical body with a tightly packed bilayer structure, where the core of the sphere is connected by Si-O chains and has a higher density, forming a cage-like SiO2, and the shell of the sphere has a lower density of R3SiO 1 / 2 layer.

[0088] Compared with other organic polymers, the cage-like SiO2 structure in the inner layer of MQ silicone resin endows the material with excellent stability, chemical corrosion resistance and excellent hydrophobicity. The organic groups in the outer layer of MQ silicone resin can endow the material with good interfacial compatibility. Compared with pure inorganic materials, it is easier to form a film coating on the positive electrode active material particles and firmly bond them. Compared with organic silane modification or silane coupling agent modification, MQ silicone resin has a more complete coating on the positive electrode active material particles and fewer interfacial defects. And the coating layer containing MQ silicone resin, because it is formed by a three-dimensional spherical structure, does not hinder the migration of lithium ions, and significantly reduces the deterioration effect on the electrochemical performance.

[0089] Generally speaking, the positive electrode active material particles in the embodiments of the present application have a polymer coating layer, which can achieve a balance between hydrophobicity and interfacial stability compared with the traditional pure inorganic or organic materials used, and further improve the hydrophobic performance of the positive electrode active material particles on the premise of ensuring good interfacial adhesion effect and electrochemical performance.

[0090] According to the embodiments of the present application, the positive electrode active material particles have a polymer coating layer, which can prevent moisture from other sources such as air from infiltrating into the positive electrode active material particles, thereby reducing the chance of contact between the positive electrode active material particles and moisture, and keeping the water content of the positive electrode active material particles at a low level.

[0091] During the use of a battery containing positive electrode active material particles, the moisture present in the electrolyte has a certain impact on the performance of the positive electrode active material particles. The positive electrode active material particles having a polymer coating layer can reduce the contact between the positive electrode active material particles and the electrolyte by reducing the contact between the positive electrode active material particles and the electrolyte, reduce the moisture obtained by the positive electrode active material particles from the electrolyte, reduce the occurrence of side reactions, and improve the stability of the positive electrode active material particles. Further, the organic groups in the outer layer of MQ silicone resin can endow the material with good interfacial compatibility, which is beneficial to the desolvation of active ions, and MQ silicone resin does not hinder the active ions from reaching the transmission, which is beneficial to the charge and discharge performance of the battery; the cage-like SiO2 structure in the inner layer of MQ silicone resin endows the material with excellent stability, chemical corrosion resistance and excellent hydrophobicity, which can improve the stability of the positive electrode active material particles, and all contribute to extending the life and cycle life of the battery or energy storage system.

[0092] The types of MQ silicone resin can be detected by commonly used methods in the art, such as nuclear magnetic resonance hydrogen spectrum and mass spectrometry.

[0093] In some alternative embodiments, the MQ silicone resin includes structural units represented by M and structural units represented by Q:

[0094]

[0095] Among them, the O in the structural unit represented by M and the structural unit represented by Q 1 / 2 represents that the oxygen atom is shared with another structural unit, and R1, R2, and R3 each independently represent hydrogen, a C1-C5 alkenyl group, a haloalkyl group, a C3-C7 acrylate group, a phenyl group, an alkyl group containing 1-6 carbon atoms that is unsubstituted or substituted by a substituent, or an alkylene oxide containing 2-4 carbon atoms; the substituent includes any one of fluorine and chlorine elements.

[0096] According to the embodiments of the present application, for the MQ silicone resin having the above structural units, a polymer coating layer is formed. The organic groups of the M structural units in the outer layer of the MQ silicone resin can endow the material with good interfacial compatibility. The groups containing the Q structure inside the MQ silicone resin have good binding properties with the matrix inside the positive electrode active material particles, enabling the MQ silicone resin to be tightly and firmly bonded to the surface of the positive electrode active material particles. And some organic groups such as methyl groups, fluorine-containing groups, and higher alkyl groups, etc., which are hydrophobic groups, can further improve the hydrophobicity of the positive electrode active material particles on the basis of the inner-layer cage-like SiO2 structure.

[0097] The above-mentioned types of hydrophobic functional groups can reduce the moisture in the air and electrolyte adsorbed by the positive electrode active material particles containing the MQ silicone resin, so that they have a lower water content during storage and use.

[0098] In some alternative embodiments, the weight-average molecular weight of the MQ silicone resin is 4000-20000, optionally 5000-10000, and optionally 6000.

[0099] According to the embodiments of the present application, when the weight-average molecular weight of the MQ silicone resin is within the above range, an appropriate amount of molecular chain segments can be obtained, which can increase the hydrophobicity of the polymer; it can also increase the bonding strength with other components in the positive electrode active material film layer, helping to reduce the probability of the positive electrode active material particles falling off during the battery cycling process, thereby improving the stability and cycle life of the battery.

[0100] The weight-average molecular weight of the MQ silicone resin within the above range is beneficial to the MQ silicone resin having a certain fluidity and cohesive strength on the surface of the positive electrode active material particles. When the weight-average molecular weight of the MQ silicone resin is too high, it is not easy to disperse and a uniform hydrophobic coating layer cannot be formed; when the weight-average molecular weight of the MQ silicone resin is too low, the adverse effects such as low cohesive strength and poor viscosity of the MQ silicone resin are also alleviated.

[0101] The weight-average molecular weight of the MQ silicone resin can be measured by methods well-known in the art. As an example, in this application, the weight-average molecular weight of the MQ silicone resin can be determined with reference to the gel permeation chromatography method of Standard GB / T21863-2008. Specifically, in this application, an ultra-high performance polymer chromatograph: ACQUITY APC (detector: ACQUITY refractive index detector) can be used and the following test steps can be carried out: (1) Power on and warm up: Install the chromatographic column and pipelines, turn on the console, test power supply, etc. in sequence, and turn on the test software Empower; (2) Parameter setting, injection volume: 0 μL to 50 μL (determined according to the sample concentration); pump flow rate: 0.2 mL / min; mobile phase: NMP solution of 30 mol / L LiBr; sealing cleaning solution: isopropanol; pre-column: PLgel 10um MiniMIX-B Guard (size: 50 mm × 4.6 mm × 2); analytical column: PLgel 10um MiniMIX-B (size: 250 mm × 4.6 mm); standard: polystyrene set; running time: 30 min; detector: ACQUITY refractive index (RI) detector; column oven temperature: 90 °C; detector temperature: 55 °C; (3) Sample test: a. Preparation of standard sample and test sample: Weigh 0.002 g to 0.004 g of standard sample / test sample respectively and add 2 mL of mobile phase liquid to prepare a mixed standard of 0.1% to 0.5%, and place it in the refrigerator for > 8 h; b. Standard solution / sample test: Edit the sample group to be measured, select the established sample group method, and click the run queue to start testing the sample after the baseline is stable; (4) Data processing: According to the relationship between the retention time and the molecular weight, use the chemical workstation to establish a calibration curve, perform integral quantification on the sample chromatogram, and the chemical workstation automatically generates the molecular weight and molecular weight distribution results.

[0102] In some alternative embodiments, the molar ratio of the structural unit represented by M and the structural unit represented by Q in the MQ silicone resin is (0.5 - 1.2):1, optionally (0.7 - 0.9):1, and optionally 0.75:1.

[0103] Optionally, the molar ratio of the structural unit represented by M and the structural unit represented by Q can be any value among 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1 or the range composed of them.

[0104] According to the embodiments of the present application, when the molar ratio of the structural unit represented by M and the structural unit represented by Q in the MQ silicone resin is within the above range, it is beneficial to the compatibility and fluidity of the MQ silicone resin. Within the above range, the larger the molar ratio, the more the content of the organic M structural unit in the silicone resin, and the better the compatibility and fluidity of the molecules. The smaller the molar ratio, the more the content of the organic Q structure in the silicone resin, and the better the strength and stability of the molecules. When the molar ratio of the MQ silicone resin in the polymer coating layer exceeds the above range, the MQ silicone resin has low strength and is easy to flow, and it is easy to form a film. However, too many organic groups are likely to accumulate and hinder the migration of active ions, especially the migration of lithium ions, affecting the kinetics of lithium batteries. When the molar ratio of the MQ silicone resin in the polymer coating layer is less than the above range, the polymer has poor compatibility, is not easy to form a film, and the polymer coating layer is easy to fall off, and the hydrophobic effect is poor.

[0105] In the embodiments of the present application, the molar ratio of the structural unit represented by M and the structural unit represented by Q in the MQ silicone resin can be determined by the type of the purchased MQ resin. It can also be determined by nuclear magnetic resonance and mass spectrometry for the types and amounts of substances of the structural units in the MQ silicone resin respectively, and then the molar ratio is determined.

[0106] In some alternative embodiments, the glass transition temperature of the MQ silicone resin is 40-200 °C. According to the embodiments of the present application, when the glass transition temperature of the MQ silicone resin is within the above range, it can have a suitable glass transition temperature; it can increase the bonding strength with other components in the positive electrode active material film layer, help reduce the probability of the positive electrode active material particles falling off during the battery cycle, and thus improve the stability and cycle life of the battery.

[0107] The glass transition temperature (Tg) is one of the characteristic temperatures of polymer materials, which refers to the temperature corresponding to the transition of the polymer material from the high elastic state to the glass state or from the glass state to the high elastic state. The glass transition temperature (Tg) can be detected by common methods in the art, such as differential scanning calorimetry (DSC), thermomechanical analysis (TMA), dynamic thermomechanical analysis (DMA), etc. of thermal analysis. Taking the DSC method to test Tg as an example, it can be detected according to the standard ISO11357-2-2013. According to the large change in specific heat before and after Tg of the MQ silicone resin, it is a step in the endothermic direction on the DSC curve. The average value of the temperatures of the two intersections of the two extrapolated baselines before and after the step with the tangent line at the inflection point of the curve is used as Tg.

[0108] In some alternative embodiments, R1, R2, and R3 each independently represent any one of hydrogen, C1-C5 alkenyl, haloalkyl, C3-C7 alkenoate group, and phenyl; optionally, the C3-C7 alkenoate includes acrylate group; optionally, the acrylate group includes any one of methyl acrylate group, ethyl acrylate group, methyl 2-methylacrylate group, and ethyl 2-methylacrylate group; optionally, the haloalkyl includes any one of trifluoromethyl and chloromethyl.

[0109] In some alternative embodiments, R1, R2, and R3 each independently represent any one of hydrogen, alkenyl, phenyl, acrylate group, trifluoromethyl, and chloromethyl.

[0110] According to the embodiments of the present application, some groups in R1, R2, and R3 have hydrophobic groups such as methyl group, fluorine-containing group, and higher alkyl group, which can further improve the hydrophobic property of the cathode active material particles on the basis of the inner-layer cage-like SiO2 structure.

[0111] In some alternative embodiments, based on the total mass of the cathode active material particles, the cathode active material particles include MQ silicone resin with a mass fraction of 0.01% to 5%.

[0112] Optionally, the cathode active material particles may include any value or a range composed of the following values of MQ silicone resin: 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.5%, 1.6%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 4.0%, 4.5%, 5.0%.

[0113] According to the embodiments of the present application, the cathode active material particles including the above content of MQ silicone resin are beneficial to form a uniform coating layer with a suitable thickness, effectively improve the hydrophobic property of the cathode active material particles, and prevent moisture from entering the inside of the cathode active material particles to reduce the water content of the cathode active material particles. Moreover, due to the double-layer spherical structure of the MQ silicone resin, the uniform polymer coating film will not significantly limit the migration of lithium ions, avoiding reducing the capacity retention rate of the battery and affecting the battery impedance.

[0114] When the content of MQ silicone resin in the positive electrode active material particles is lower than the above range, a complete coating layer may not be formed, resulting in a poor coating effect and reduced hydrophobic performance. On the other hand, the incomplete coating or the existence of defects may cause the MQ silicone resin to not adhere tightly to the matrix inside the positive electrode active material particles, and may easily lead to the detachment of the MQ silicone resin under the action of external forces or other factors, even causing the coating layer to lose its function. On the contrary, when the content of MQ silicone resin in the positive electrode active material particles exceeds the above range, the coating layer will be too thick, which may hinder the transport of lithium ions in the lithium battery, affect the migration rate of lithium ions, and thus affect the battery kinetics.

[0115] According to the embodiments of the present application, when the MQ silicone resin in the positive electrode active material particles is within the above suitable range, while taking into account the battery kinetics performance, the contact between the positive electrode active material particles and the electrolyte can be reduced, the moisture in the electrolyte can be reduced, the occurrence of side reactions can be decreased, and the stability and cycle life of the positive electrode active material particles can be improved. Compared with the uncoated positive electrode active material particles, the positive electrode active material particles with the above coating layer have better surface elasticity, which can further improve the adhesion and cohesion of the positive electrode sheet. Therefore, by further controlling the coating amount, better battery cycle performance and low anti-swelling performance can be obtained.

[0116] According to the embodiments of the present application, when the MQ silicone resin in the positive electrode active material particles is within the above suitable range, it ensures that the positive electrode active material particles have a high proportion of positive electrode active material particles, enabling the positive electrode sheet to have good lithium ion conductivity and electron conductivity. Therefore, using this positive electrode sheet in a lithium battery can significantly improve the energy density, rate performance, and cycle performance of the battery.

[0117] The detection method for the content of MQ silicone resin in the positive electrode active material particles can be measured by TGA (thermogravimetric analysis).

[0118] As an example, the test method can be as follows: Add 5 - 10 mg of the sample into a crucible, under an argon atmosphere, heat the temperature from 50 to 600 °C at a heating rate of 10 °C / min, and record the residual mass at 600 °C. The calculation formula for the content of MQ silicone resin is: Content of MQ silicone resin = (Residual mass of modified positive electrode active material particles - Residual mass of unmodified positive electrode active material raw material particles) / (Residual mass of modified positive electrode active material particles containing MQ resin)

[0119] In the embodiments of the present application, the water content of the positive electrode active material particles can be measured by the Karl Fischer method well-known in the art. In some alternative embodiments, the water content of the positive electrode active material particles < 1200 ppm. The water content of the positive electrode active material particles can be 1 ppm, 5 ppm, 10 ppm, 20 ppm, 30 ppm, 40 ppm, 50 ppm, 60 ppm, 70 ppm, 80 ppm, 90 ppm, 100 ppm, 110 ppm, 120 ppm, 130 ppm, 140 ppm, 150 ppm, 160 ppm, 170 ppm, 180 ppm, 190 ppm, 200 ppm, 300 ppm, 400 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm, 1100 ppm, 1199 ppm or any value within the range composed thereof.

[0120] According to the embodiments of the present application, the positive electrode active material particles have a polymer coating layer, and the water content thereof is within the above range, which improves the stability of the positive electrode active material particles.

[0121] In some alternative embodiments, the encapsulation rate of the polymer coating layer ≥ 90%.

[0122] The encapsulation rate is defined as the percentage of the coverage area of the surface modifier molecules on the surface of the powder (particles) to the total surface area of the powder (particles). The method for detecting the encapsulation rate of the positive electrode active material particles can adopt the methods commonly used in the art. As an example, the monolayer encapsulation of the surface modifier molecules on the powder surface can calculate the surface encapsulation rate n = (M * N A * a) / (q * S), where n is the encapsulation rate, M is the content of MQ silicone resin, q is the molecular weight of the silicone resin, N A is Avogadro's constant, a is the cross-sectional area of the coating layer, and S is the specific surface area of the positive electrode active material particles.

[0123] It should be noted that for some MQ silicone resin systems, such as methyl or vinyl MQ silicone resin itself is easy to form a film, and a binder may not be used. For some MQ silicone resins that are difficult to form a film, a suitable binder needs to be added according to the peripheral groups of the silicone resin used. In some alternative embodiments, the positive electrode active material particles include a binder; optionally, based on the total mass of the positive electrode active material particles, the positive electrode active material particles include 0 to 2.5% binder.

[0124] According to the embodiments of the present application, the binder has good compatibility with some groups in the MQ silicone resin or has a structural feature similar to that of the MQ silicone resin, and thus can promote the formation of a complete and uniform polymer coating layer of the MQ silicone resin, improving the integrity and uniformity of the coating of the positive electrode active material particles.

[0125] In some alternative embodiments, the mass ratio of the binder to the MQ silicone resin is (0.01 - 0.5):1, and can be optionally (0.1 - 0.25):1.

[0126] According to the embodiments of the present application, when the mass ratio of the binder to the MQ silicone resin is within the above range, the binder can promote the formation of a complete and uniform polymer coating layer of the MQ silicone resin, improving the integrity and uniformity of the coating of the positive electrode active material particles. When the mass ratio of the binder to the MQ silicone resin is lower than the above range, the formed polymer coating layer is uneven and easily falls off, and cannot achieve a good hydrophobic effect; on the contrary, when the mass ratio of the binder to the MQ silicone resin is higher than the above range, the mass ratio of organic components such as the binder in the coating layer is higher than the above range, which not only cannot prevent moisture from entering the positive electrode active material particles, but also affects the kinetic process of the lithium battery.

[0127] In the embodiments of the present application, the mass ratio of the binder to the MQ silicone resin can be determined by the addition amount during preparation. It can also be determined by separately determining the amounts of the two organic substances through nuclear magnetic resonance and mass spectrometry.

[0128] In some alternative embodiments, the binder includes one or more of acrylic binders, polyurethane binders, silicone binders, polyvinylidene fluoride binders, and epoxy resin binders. As an example, the silicone binder includes styrene-butadiene rubber, and its weight average molecular weight is 20,000 - 1,000,000.

[0129] According to the embodiments of the present application, the above types of binders have a good promoting effect on MQ silicone resins with compatible peripheral groups or group characteristics similar to those of the binder, and can promote the formation of a complete and uniform polymer coating layer of the MQ silicone resin, improving the integrity and uniformity of the coating of the positive electrode active material particles.

[0130] In some alternative embodiments, the average thickness of the polymer coating layer is 100 nm to 200 nm. Optionally, the average thickness of the coating layer can be any value among 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm or the range composed of them.

[0131] According to the embodiments of the present application, when the amount of the polymer coating layer is controlled within a certain range, on the premise of taking into account the battery kinetic performance, the contact between the positive electrode active material particles and the electrolyte can be reduced, the moisture in the electrolyte can be reduced, the occurrence of side reactions can be reduced, and the stability and cycle life of the positive electrode active material particles can be improved. Compared with the uncoated positive electrode active material particles, the positive electrode active material particles with the above polymer coating layer have better surface elasticity, which can further improve the adhesion and cohesion of the positive electrode sheet. Therefore, by further controlling the polymer coating amount, better battery cycle performance and low anti-swelling performance can be obtained.

[0132] The average thickness of the coating layer can be calculated by sampling and detecting the average thickness of the coating layer in the cross-section of the positive electrode active material particles.

[0133] In some optional embodiments, the positive electrode active material particles have a core-shell structure in which the coating layer coats the positive electrode active material core.

[0134] According to the embodiments of the present application, the positive electrode active material particles with a core-shell structure obtain a relatively complete and uniform coating, which can prevent moisture from penetrating into the interior of the positive electrode active material particles, reduce the overall moisture content of the positive electrode active material particles, and thus reduce the chance of contact between the positive electrode active material particles and moisture. The shell contains a polymer, which reduces the contact between the positive electrode active material particles and the electrolyte, can reduce the moisture in the electrolyte, reduce the occurrence of side reactions, and improve the stability of the positive electrode active material particles.

[0135] The positive electrode active material particles implemented in the present application can be materials commonly used in the art, and there are no obvious restrictions on them.

[0136] In some optional embodiments, the positive electrode active material particles include one or more of a layered metal oxide material, an olivine-type positive electrode material, and a spinel-type material; optionally, the olivine-type positive electrode material includes a lithium iron phosphate material; optionally, the positive electrode active material particles include one or more of a lithium nickel cobalt manganese oxide material and a lithium nickel cobalt aluminum oxide material.

[0137] According to the embodiments of the present application, the commonly used positive electrode active material particles include the above types. The surface of the positive electrode active material particles of the above types has a specific polymer coating layer, which can reduce the overall moisture content of the positive electrode active material particles, reduce the occurrence of side reactions, and improve the stability of the positive electrode active material particles.

[0138] The modification compounds of the above positive electrode active material particles can be doping modification and / or surface coating modification of the positive electrode active material.

[0139] As an example, the layered metal oxide material in the positive electrode active material particles includes lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2). As an example, the spinel-type material in the positive electrode active material particles includes lithium iron phosphate (LiFePO4) and lithium manganese oxide (LiMn2O4). As an example, the olivine-type positive electrode material in the positive electrode active material particles includes lithium titanate (LiTiO2). As an example, the mixed structure material or ternary positive electrode material in the positive electrode active material particles includes lithium nickel cobalt manganese oxide (LiNi x Co y Mn 1-x-y O2) and lithium nickel cobalt aluminum oxide (LiNi x Co y Al 1-x-y O2), where x and y are 0.01 to 0.99 respectively.

[0140] For example, when the battery cell is a lithium-ion battery cell or a lithium metal battery cell, the positive electrode active material may include one or more of lithium transition metal oxides, lithium-containing phosphates with an olivine structure, and their respective modified compounds. Examples of lithium transition metal oxides may include one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of lithium-containing phosphates with an olivine structure may include one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, a composite material of lithium manganese iron phosphate and carbon, and their respective modified compounds. The present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials may also be used.

[0141] In some embodiments, in order to further improve the energy density of the battery cell, the positive electrode active material may include one or more of lithium transition metal oxides represented by the general formula Li a Ni b Co c M d O e A f and their modified compounds. 0.8 ≤ a ≤ 1.2, 0.5 ≤ b < 1, 0 < c < 1, 0 < d < 1, 1 ≤ e ≤ 2, 0 ≤ f ≤ 1, M includes one or more selected from Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, and A includes one or more selected from N, F, S, and Cl.

[0142] As an example, the positive electrode active material may include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3Mn 1 / 3O2 (NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), LiNi 0.80 Co 0.15 Al 0.05 O2, LiFePO4, and one or more of LiMnPO4.

[0143] When the battery cell is a sodium-ion battery cell or a sodium metal battery cell, the positive electrode active material may include, but is not limited to, one or more of sodium-containing transition metal oxides, polyanion materials (such as phosphates, fluorophosphates, pyrophosphates, sulfates, etc.), and Prussian blue-based materials.

[0144] As an example, the positive electrode active material may include NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, NaNi 1 / 2Ti 1 / 2 O2, NaNi 1 / 2 Mn 1 / 2 O2, Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2, NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, NaFePO4, NaMnPO4, NaCoPO4, Prussian blue-based materials, and materials of the general formula X p M’ q (PO4) r O x Y 3-x and one or more of the materials of. In the general formula X p M’ q (PO4) r O x Y 3-x , 0 < p ≤ 4, 0 < q ≤ 2, 1 ≤ r ≤ 3, 0 ≤ x ≤ 2, X includes selected from H + , Li + , Na + , K + and NH4 +One or more of them, M’ is a transition metal cation, optionally including one or more selected from V, Ti, Mn, Fe, Co, Ni, Cu, and Zn, and Y is a halogen anion, optionally including one or more selected from F, Cl, and Br.

[0145] According to the embodiments of the present application, the MQ silicone resin of the present application has excellent universality for the types of cathode active material in the cathode active material particles. Due to the chemically stable and relatively high-density cage-like SiO2 structure of the MQ silicone resin and various optional organic groups on the periphery, the MQ silicone resin can be applied to all current cathode active materials to form a well-compatible and uniform hydrophobic coating layer, thereby having a certain hydrophobic modification effect on the existing cathode active material particles.

[0146] In some optional embodiments, the average particle size Dv50 of the cathode active material particles is 0.52 μm to 4.1 μm, optionally 0.9 μm to 1.9 μm.

[0147] Optionally, any value among 0.52 μm, 0.6 μm, 0.7 μm, 0.8 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.1 μm or the range composed of them.

[0148] According to the embodiments of the present application, the cathode active material particles with the above average particle size are beneficial to the electrochemical performance in the cathode electrode sheet, and also have a relatively high specific surface area to increase the capacity of the battery, improve the energy density of the battery, and enable it to store more electric energy. The cathode active material particles with the above average particle size contribute to the ion and electron transport between the electrolyte and the cathode active material particles, and can improve the charge and discharge speed of the battery. The cathode active material particles with the above average particle size can reduce the stress of the electrode, reduce the volume expansion and contraction of the material, thereby reducing the loss of the battery during the cyclic charge and discharge process and extending the life of the battery.

[0149] The average particle size distribution Dv50 of the cathode active material particles, the average particle size distribution Dv of the cathode active material particles 2 50 has the meaning well-known in the art. The particle size distribution Dv50 is also called the average particle size or the median particle size, which represents the particle size corresponding to 50% of the volume distribution of the cathode active material particles. The above particle size distributions can be measured by instruments and methods well-known in the art. For example, it can be conveniently measured with a laser particle size analyzer, such as the Mastersizer 3000 type laser particle size analyzer of Malvern Instruments Limited in the UK.

[0150] In some optional embodiments, the specific surface area of the cathode active material particles is 7 m 2 / g to 15 m 2 / g, optionally 10 m 2 / g to 13 m 2 / g.

[0151] Optionally, the specific surface area of the positive electrode active material particles can be 7 m 2 / g, 8 m 2 / g, 9 m 2 / g, 10 m 2 / g, 11 m 2 / g, 12 m 2 / g, 13 m 2 / g, 14 m 2 / g, 15 m 2 Any value within / g or the range composed thereof.

[0152] According to the embodiments of the present application, when the specific surface area of the positive electrode active material particles is within the above range, it means that there are more active sites available for electrochemical reactions, so the capacity of the battery is larger, and the energy density of the battery can also be improved; the above larger specific surface area has more active surfaces, which can accelerate the transport of ions and electrons in the electrolyte, thereby reducing the charging and discharging time, and contributing to improving the charging and discharging speed of the battery. The above larger specific surface area is usually accompanied by a more uniform utilization of the electrode material, reducing material loss and contributing to extending the battery life.

[0153] The specific surface area of the positive electrode active material particles has the meaning well-known in the art and can be measured by the instruments and methods well-known in the art. For example, it can be measured with reference to the standard for measuring the specific surface area of solid substances by the gas adsorption BET method in GB / T19587-2004, tested by the nitrogen adsorption specific surface area analysis test method, and calculated by the BET (Brunauer Emmett Teller) method. Among them, the nitrogen adsorption specific surface area analysis test can be carried out by the TriStarⅡ3020 specific surface area and pore size analyzer of Micromeritics Company, USA.

[0154] Preparation method of positive electrode active material particles

[0155] In a second aspect, the embodiments of the present application provide a preparation method of positive electrode active material particles with a polymer coating layer, including:

[0156] Providing a mixture containing positive electrode active material raw material particles, MQ silicone resin and a solvent;

[0157] Drying the mixture to form a polymer coating layer coating the positive electrode active material raw material particles.

[0158] According to the embodiments of the present application, the raw material particles of the positive electrode active material can be understood as the conventional positive electrode active material particles without a polymer coating layer or the raw materials purchased from suppliers, which are the commonly used positive electrode active materials in the art. The MQ silicone resin, the polymer coating layer, and the positive electrode active material particles can be the MQ silicone resin, the polymer coating layer, and the positive electrode active material particles described in any of the above embodiments, which will not be elaborated here.

[0159] According to the embodiments of the present application, as the main component of the coating layer of the positive electrode active material particles, the MQ silicone resin has a hydrophobic effect. The MQ silicone resin is a kind of organosilicon resin with a relatively unique three-dimensional spherical structure, which can include an M structure with monofunctionality, and the organosiloxane closed chain segment R3SiO 1 / 2 And the polysiloxane formed with the Q structure with tetrafunctionality. Generally, the MQ silicone resin is a spherical body with a tightly packed double-layer structure, in which the core of the sphere is connected by Si—O chains and has a higher density, forming a cage-like SiO2, and the shell of the sphere is the R3SiO 1 / 2 layer.

[0160] Compared with other organic polymers, the inner cage-like SiO2 structure of the MQ silicone resin endows the material with excellent stability, chemical corrosion resistance, and excellent hydrophobicity. The organic groups on the outer layer of the MQ silicone resin can endow the material with good interfacial compatibility. Compared with pure inorganic materials, it is easier to form a film on the positive electrode active material particles and firmly bond. Compared with organosilane modification or silane coupling agent modification, the MQ silicone resin coats the positive electrode active material particles more completely and has fewer interfacial defects. And the coating layer containing the MQ silicone resin is composed of a three-dimensional spherical structure stacked together, which does not hinder the migration of lithium ions and reduces the deterioration effect on the electrochemical performance. Generally speaking, the positive electrode active material particles of the embodiments of the present application have a polymer coating layer, which can achieve a balance between hydrophobicity and interfacial stability compared with the traditional pure inorganic or organic materials used, and further improve the hydrophobic performance of the positive electrode active material particles on the premise of ensuring good interfacial adhesion effect and electrochemical performance.

[0161] According to the embodiments of the present application, the positive electrode active material particles with a polymer coating layer can prevent moisture from other sources such as air from infiltrating into the positive electrode active material particles, thereby reducing the chance of contact between the positive electrode active material particles and moisture and keeping the water content of the positive electrode active material particles at a low level.

[0162] When the positive electrode active material particles are used in a battery, the moisture present in the electrolyte has a certain impact on the performance of the positive electrode active material particles. The positive electrode active material particles have a polymer coating layer. By reducing the contact between the positive electrode active material particles and the electrolyte, the positive electrode active material particles can obtain less moisture in the electrolyte, reducing the occurrence of side reactions and improving the stability of the positive electrode active material particles. Further, the organic groups on the outer layer of MQ silicone resin can endow the material with good interfacial compatibility, which is beneficial to the desolvation of active ions. And MQ silicone resin does not hinder the active ions from reaching and transporting, which is beneficial to the charge and discharge performance of the battery; the cage-like SiO2 structure on the inner layer of MQ silicone resin endows the material with excellent stability, chemical corrosion resistance and excellent hydrophobicity, which can improve the stability of the positive electrode active material particles, all of which contribute to extending the life and cycle life of the battery or energy storage system.

[0163] In some alternative embodiments, the mass ratio of the MQ silicone resin to the raw positive electrode active material particles is (0.01 - 5):100.

[0164] Optionally, the mass ratio of the MQ silicone resin to the raw positive electrode active material particles can be any value or a range composed of 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.1:1,, 0.15:1, 0.2:1, 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1, 0.5:1, 0.6:10.61:1, 0.65:1, 0.7:1, 0.75:1, 0.8:1, 0.85:1, 0.9:1, 0.95:1, 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 2.0:1, 3.0:1, 4.0:1, 5.0:1.

[0165] According to the embodiments of the present application, when the mass ratio of the MQ silicone resin to the raw positive electrode active material particles is within the above range, it is beneficial to form a uniform polymer coating layer with a suitable thickness, effectively improving the hydrophobic performance of the positive electrode active material particles and preventing moisture from entering the interior of the positive electrode active material particles to reduce the water content of the positive electrode active material particles. And due to the double-layer spherical structure of MQ silicone resin, the uniform polymer coating film will not significantly limit the migration of lithium ions, avoiding reducing the capacity retention rate of the battery and affecting the battery impedance.

[0166] In some embodiments, the solvent includes one or more of N-methylpyrrolidone, ethanol, ethyl acetate, and dichloromethane.

[0167] According to the embodiments of the present application, solvents of the above types can be compatible with MQ silicone resin, enabling the MQ silicone resin and the solvent to effectively and uniformly exist in the form of a liquid in the positive electrode active material raw material particles, facilitating the subsequent formation of a uniform polymer coating layer.

[0168] Positive electrode plate

[0169] In a third aspect, embodiments of the present application provide a positive electrode plate, including a positive electrode current collector and a positive electrode active material film layer disposed on at least one side of the positive electrode current collector. The positive electrode active material film layer includes the positive electrode active material particles of the first aspect or the positive electrode active material particles prepared by the preparation method of the second aspect.

[0170] According to the embodiments of the present application, the positive electrode plate contains the above positive electrode active material particles, which is conducive to the formation of a uniform positive electrode active material film layer. The water content of the positive electrode active material particles therein is relatively low. Existing in the positive electrode active material film layer, it can improve the stability of the positive electrode plate during the use of the battery, and help extend the life of the battery or energy storage system. The polymer on the surface of the positive electrode active material particles can reduce the contact between the positive electrode active material particles and the electrolyte, reduce the positive electrode active material particles from obtaining moisture in the electrolyte, reduce the occurrence of side reactions, and is beneficial to the cycling performance.

[0171] In some optional embodiments, based on the total weight of the positive electrode active material film layer, the positive electrode active material film layer includes: 85% - 98.7% of positive electrode active material particles, optionally 91.5% - 98.3%. Positive electrode active material particles with the above mass content can increase the total capacity of the battery, enable the battery to store more electrical energy, and extend the battery life.

[0172] In some optional embodiments, based on the total weight of the positive electrode active material film layer, the positive electrode active material film layer includes 0.7% - 6% of polymer or 0.7% - 6% of binder, optionally 1% - 2.5%; or 1% - 2.5% of polymer or binder. When the positive electrode active material film layer has the above polymer or binder, the positive electrode active material film layer has a certain cohesive strength, which can improve the flexibility of the positive electrode active material film layer and reduce the probability of fracture or cracking caused by winding or folding of the positive electrode active material film layer.

[0173] In some optional embodiments, the positive electrode active material film layer further includes a conductive agent. In some optional embodiments, based on the total weight of the positive electrode active material film layer, the positive electrode active material film layer includes: 0.4% - 10% of conductive agent, optionally 0.7% - 5%. It can reduce the internal resistance of the positive electrode plate and improve the charge and discharge efficiency.

[0174] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material film layer provided on at least one surface of the positive electrode current collector and including a positive electrode active material. For example, the positive electrode current collector has two surfaces opposite to each other in its own thickness direction, and the positive electrode active material film layer is provided on either or both of the two opposite surfaces of the positive electrode current collector.

[0175] The positive electrode active material film layer includes positive electrode active material particles, and the positive electrode active material particles can be the positive electrode active materials for battery cells known in the art.

[0176] In some embodiments, the positive electrode active material film layer may further optionally include a positive electrode conductive agent. There is no particular limitation on the type of the positive electrode conductive agent in this application. As an example, the positive electrode conductive agent includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0177] In some embodiments, the positive electrode active material film layer may further optionally include a positive electrode binder. There is no particular limitation on the type of the positive electrode binder in this application. As an example, the positive electrode binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins.

[0178] In some embodiments, the positive electrode current collector can be a metal foil or a composite current collector. As an example of the metal foil, aluminum foil can be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0179] The positive electrode active material film layer is usually formed by coating a positive electrode slurry on the positive electrode current collector and then drying and cold pressing. The positive electrode slurry is usually formed by dispersing a positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring evenly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.

[0180] In some embodiments, the method for preparing the positive electrode active material film layer includes:

[0181] Providing a slurry containing a binder, a positive electrode active material, and a conductive agent;

[0182] Coat with a slurry and dry it to form a positive electrode active material film layer. In some embodiments, when the solid content of the slurry is ≥75%, the leveling property of the slurry disappears, and it can be calendered into a film by a calender; the increase of the solid content can effectively reduce the drying energy consumption and lower the production cost.

[0183] In some embodiments, based on the total mass of the positive electrode active material, conductive agent, and binder, the total addition amount of the binder is preferably 1% - 2.5 wt%, such as 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%.

[0184] Battery cell

[0185] Fourthly, an embodiment of the present application provides a battery cell, including the positive electrode sheet of the third aspect. The battery cell of the embodiment of the present application includes the above positive electrode sheet, which helps to extend the life and cycling performance of the battery.

[0186] The present application does not particularly limit the type of the battery cell. For example, the battery cell can be a lithium-ion battery, a sodium-ion battery, etc. Optionally, it can be a lithium-ion battery.

[0187] In some embodiments, the battery cell includes a negative electrode sheet, a separator, and an electrolyte.

[0188] [Negative electrode sheet]

[0189] The specific composition and structure of the negative electrode sheet can be selected according to the type of the battery cell, and the embodiments of the present application do not limit this.

[0190] For example, when the battery cell is a lithium-ion battery cell or a sodium-ion battery cell, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material film layer provided on at least one surface of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material film layer is provided on any one or both of the two opposite surfaces of the negative electrode current collector.

[0191] The negative electrode active material is a material capable of deintercalating and intercalating active ions (such as lithium ions, sodium ions, etc.). The negative electrode active material can adopt materials well-known in the art. As an example, the negative electrode active material includes, but is not limited to, one or more of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based materials can include one or more of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloy materials. The tin-based materials can include one or more of elemental tin, tin oxides, and tin alloy materials. The present application is not limited to these materials, and other conventionally well-known materials that can be used as the negative electrode active material can also be used.

[0192] In some embodiments, the negative electrode active material film layer may further optionally include a negative electrode conductive agent. The present application does not particularly limit the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0193] In some embodiments, the negative electrode active material film layer may further optionally include a negative electrode binder. The present application does not particularly limit the type of the negative electrode binder. As an example, the negative electrode binder may include one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).

[0194] In some embodiments, the negative electrode active material film layer may further optionally include other additives. As an example, the other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC-Na), PTC thermistor materials, etc.

[0195] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0196] The negative electrode active material film layer is usually formed by coating a negative electrode slurry on the negative electrode current collector and then drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional additives in a solvent and stirring evenly. The solvent may be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.

[0197] The negative electrode plate does not exclude other additional functional layers other than the negative electrode active material film layer. For example, in some embodiments, the negative electrode plate of the present application may further include a conductive bottom layer (e.g., composed of a conductive agent and a binder) disposed on the surface of the negative electrode current collector and sandwiched between the negative electrode current collector and the negative electrode active material film layer; in some embodiments, the negative electrode plate of the present application may further include a protective layer covering the surface of the negative electrode active material film layer.

[0198] When the battery cell is a lithium metal battery cell, the negative electrode sheet may not include a negative electrode active material capable of deintercalating and intercalating active ions. For example, in some embodiments, the negative electrode sheet may include a lithium sheet or a lithium alloy sheet; in other embodiments, the negative electrode sheet includes a networked or foamed three-dimensional skeleton layer, such as, for example, copper foam (or copper alloy), nickel foam (or nickel alloy), copper (or copper alloy) mesh, nickel (or nickel alloy) mesh, etc.

[0199] When the battery cell is a sodium metal battery cell, the negative electrode sheet may not include a negative electrode active material capable of deintercalating and intercalating active ions. For example, in some embodiments, the negative electrode sheet may include a sodium sheet or a sodium alloy sheet; in other embodiments, the negative electrode sheet includes a networked or foamed three-dimensional skeleton layer, such as, for example, copper foam (or copper alloy), nickel foam (or nickel alloy), aluminum foam (or aluminum alloy), copper (or copper alloy) mesh, nickel (or nickel alloy) mesh, aluminum (or aluminum alloy) mesh, etc.

[0200] [Preparation Method]

[0201] The preparation method of the battery of the present application is well-known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet, and the electrolyte may be assembled to form a battery cell. As an example, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly through a winding process and / or a stacking process, the electrode assembly is placed in an outer package, dried, and then the electrolyte is injected, and after processes such as encapsulation, standing, formation, and shaping, a battery cell is obtained. Multiple battery cells may further be combined in series or in parallel or in a hybrid connection to form a battery module. Multiple battery modules may further form a battery pack through series or parallel or hybrid connection. In some embodiments, multiple battery cells may also directly form a battery pack.

[0202] [Separator]

[0203] The separator is disposed between the positive electrode sheet and the negative electrode sheet, and mainly functions to prevent short circuit between the positive electrode and the negative electrode. The present application does not particularly limit the type of the separator, and any well-known porous structure separator having good chemical stability and mechanical stability may be selected.

[0204] In some embodiments, the material of the separator may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer are the same or different.

[0205] [Electrolyte]

[0206] In some embodiments, the battery cell includes an electrolyte. The electrolyte functions to conduct active ions between the positive electrode sheet and the negative electrode sheet. There is no specific limitation on the type of the electrolyte in this application, and it can be selected according to requirements. For example, the electrolyte can be selected from at least one of solid electrolytes and liquid electrolytes (i.e., electrolytic solutions).

[0207] In some embodiments, the electrolyte used is an electrolytic solution. The electrolytic solution includes an electrolyte salt and a solvent.

[0208] The type of the electrolyte salt is not specifically limited and can be selected according to actual requirements. For example, the electrolyte salt includes one or more selected from lithium salts for lithium-ion batteries and sodium salts for sodium-ion batteries. As an example, the lithium salts include one or more selected from lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluoro(oxalato)borate (LiDFOB), lithium bis(oxalato)borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluoro(dioxalato)phosphate (LiDFOP), and lithium tetrafluoro(oxalato)phosphate (LiTFOP). As an example, the sodium salts include one or more selected from NaPF6, NaClO4, NaBCl4, NaSO3CF3, and Na(CH3)C6H4SO3.

[0209] The type of the solvent is not specifically limited and can be selected according to actual requirements. In some embodiments, as an example, the solvent can include one or more selected from ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS), and diethyl sulfone (ESE).

[0210] In some embodiments, the electrolytic solution may optionally further include additives. For example, the additives can include negative electrode film-forming additives, or can include positive electrode film-forming additives, or can also include additives that can improve certain performances of the battery, such as additives for improving the overcharge performance of the battery, additives for improving the high-temperature performance of the battery, additives for improving the low-temperature power performance of the battery, etc.

[0211] In some embodiments, the battery cell may include an outer package. The outer package may be used to encapsulate the above-mentioned electrode assembly and electrolyte.

[0212] In some embodiments, the outer package of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the battery cell may also be a soft package, such as a pouch soft package. The material of the soft package may be plastic, such as one or several of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.

[0213] The present application places no particular limitation on the shape of the battery cell, which may be a flat body, a cuboid or other shapes. As Figure 1 is a battery cell 5 having a cuboid structure as an example.

[0214] In some embodiments, as Figure 2 shown, the outer package may include a housing 51 and a cover plate 53. It is characterized in that the housing 51 may include a bottom plate and side plates connected to the bottom plate, and the bottom plate and the side plates enclose to form a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The electrode assembly 52 of the first aspect of the embodiment of the present application or the electrode assembly 52 prepared by the method of the second aspect of the embodiment of the present application is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 included in the battery cell 5 may be one or several, and can be adjusted according to requirements.

[0215] The preparation method of the battery cell of the present application is well-known, and the method at least includes the step of preparing the electrode assembly in the second aspect of the embodiment of the present application. In some embodiments, the electrode assembly may be placed in the outer package, dried and then injected with electrolyte, and after processes such as vacuum packaging, standing, forming, shaping, etc., a battery cell is obtained.

[0216] In a fifth aspect, an embodiment of the present application provides a battery, including the battery cell of the fourth aspect. The battery can be understood as a battery module or a battery pack.

[0217] In some embodiments of the present application, the battery cells according to the present application can be assembled into a battery module, and the number of battery cells included in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.

[0218] Optionally, the battery module may further include a housing having a receiving space, and a plurality of battery cells are received in the receiving space.

[0219] In some embodiments, the above-mentioned battery module can be further assembled into a battery pack, and the number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0220] Electrical device

[0221] In a sixth aspect, an embodiment of the present application provides an electrical device including the battery of the fifth aspect.

[0222] The battery cell including the positive electrode active material and the electrical device of the battery at least have the above advantages.

[0223] The battery cell or the electrical device of the present application includes the separator of the first aspect of the present application, and thus at least has the advantages of the application of the separator.

[0224] The battery cell can be used as the power source of the electrical device or as the energy storage unit of the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.

[0225] Figure 3 It is a schematic diagram of an electrical device as an example. The electrical device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electrical device for high power and high energy density, a battery pack or a battery module can be used.

[0226] Another example of the electrical device can be a mobile phone, a tablet computer, a laptop computer, etc. The electrical device usually requires thinning, and a battery cell can be used as the power source.

[0227] Embodiment

[0228] The following embodiments more specifically describe the content disclosed in the present application. These embodiments are only for illustrative purposes, because various modifications and changes within the scope of the content disclosed in the present application are obvious to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and all instruments used in the embodiments are commercially available.

[0229] Example 1

[0230] Preparation of cathode active material particles: Using 100 g by mass of lithium iron phosphate (LiFePO4) as the raw material particles of the cathode active material, dissolve 1 g by mass of methyl MQ silicone resin with an M / Q value of 0.75 and a molecular weight of 6000 in 100 g by mass of N-methylpyrrolidone, and stir at a speed of 1000 rpm for 30 min at 25 °C to obtain a uniform solution; then add 100 g of lithium iron phosphate powder and stir at a speed of 2000 rpm for 60 min to obtain a uniform mixed system; filter to remove the excess solvent, and then dry the above-mentioned cathode active material particles loaded with MQ silicone resin in a vacuum oven at 105 °C for 24 h to obtain a solid mixture; grind the above-mentioned solid mixture to obtain cathode active material particles. The structural formula of MQ silicone resin is [(CH3)3SiO 1 / 2 a [SiO 4 / 2 b , where a and b are positive integers respectively.

[0231] Preparation of the cathode electrode sheet:

[0232] Using the prepared modified lithium iron phosphate as the cathode active material particles, after thoroughly stirring and mixing the cathode active material particles, polyvinylidene fluoride, and conductive carbon black in a mass ratio of 72:2.3:0.5, add N-methylpyrrolidone to obtain a cathode slurry, and the solid content of the slurry is 64%; then evenly coat the cathode slurry on the cathode current collector, and after drying, cold pressing, and slitting, obtain the cathode electrode sheet corresponding to Example 1.

[0233] Preparation of the lithium-ion battery:

[0234] Negative electrode sheet: Using a graphite negative electrode, the conductive agent is conductive carbon black; the binder is a 1:1 mixture of styrene-butadiene rubber and sodium carboxymethyl cellulose. Among them, the ratio of graphite material: conductive carbon black: binder = 96:2:2.

[0235] Electrolyte: 1M LiPF6, the solvent is ethylene carbonate (EC) and ethyl methyl carbonate (EMC), where EC / DEC (volume ratio 3:7).

[0236] Separator: Using a polyethylene separator with a thickness of 12 μm, sourced from Shenzhen Zhongxing New Materials Technology Co., Ltd.

[0237] Stack the prepared cathode electrode sheet, separator, and negative electrode sheet in sequence, with the separator placed between the positive and negative electrode sheets to play a separating role, then wind to obtain a bare battery cell, weld the tabs to the bare battery cell, and place the bare battery cell into an aluminum shell, and bake to remove water at 80 °C, then immediately inject the electrolyte and seal to obtain a non-charged battery. The non-charged battery is then successively subjected to processes such as standing, hot and cold pressing, formation, shaping, and capacity testing to obtain the lithium-ion battery product.​​

[0238] Examples 2 - 4

[0239] The difference between this example and Example 1 lies in that the M / Q value of the MQ silicone resin is different, and the other steps of Examples 2 - 4 are the same as those of Example 1.

[0240] Examples 5 - 7

[0241] The difference between this example and Example 1 lies in that the mass ratio of the added MQ silicone resin to the raw material particles of the positive electrode active material is different, and the other steps of Examples 5 - 7 are the same as those of Example 1.

[0242] Examples 8 - 10

[0243] The difference between this example and Example 1 lies in that the type of the MQ silicone resin is different, and the other steps are the same as those of Example 1. The structural formula of the MQ silicone resin in Example 8 is [(CH2=CH)3SiO 1 / 2 a [SiO 4 / 2 b , the structural formula of the MQ silicone resin in Example 9 is [(CH3)2CH2=CHSiO 1 / 2 a [SiO 4 / 2 b , the structural formula of the MQ silicone resin in Example 9 is [(C 12 H 25 )3SiO 1 / 2 a [SiO 4 / 2 b , where a and b are positive integers respectively.

[0244] Example 11

[0245] The difference between this example and Example 1 lies in that the type of the MQ silicone resin is different, and the structural formula of the MQ silicone resin is [(C6H5)3SiO 1 / 2 a [SiO 4 / 2 b , where a and b are positive integers respectively. During the preparation process: 0.01 g of styrene - butadiene rubber from Beijing Zhonglai Chemical Co., Ltd. was dissolved in 100 g by mass of N - methylpyrrolidone.

[0246] Example 12

[0247] The difference between this example and Example 11 lies in that the type of the MQ silicone resin is different, and the structural formula of the MQ silicone resin is [(CH3)3SiO 1 / 2 a [SiO 4 / 2 ​​​​​​​​​​b , a, and b are positive integers respectively.

[0248] Example 13

[0249] The difference between this example and Example 12 is as follows: During the preparation process, 0.1 g of styrene-butadiene rubber from Beijing Zhonglai Chemical Co., Ltd. was dissolved in 100 g by mass of N-methylpyrrolidone.

[0250] Example 14

[0251] The difference between this example and Example 12 is as follows: During the preparation process, 0.2 g of styrene-butadiene rubber from Beijing Zhonglai Chemical Co., Ltd. was dissolved in 100 g by mass of N-methylpyrrolidone.

[0252] Example 15

[0253] The difference between this example and Example 12 is that the structural formula of the MQ silicone resin is [H3SiO 1 / 2 a [SiO 4 / 2 b , a, and b are positive integers respectively. During the preparation process, the binder was changed to silicone rubber from Dow Corning Corporation, USA, with a molecular weight of 50,000 and the silicone rubber grade of DC184.

[0254] Example 16

[0255] The difference between this example and Example 12 is that the structural formula of the MQ silicone resin is [(CH2=CH)3SiO 1 / 2 a [SiO 4 / 2 b , a, and b are positive integers respectively. During the preparation process, the binder was changed to polyurethane from Wanhua Chemical Group Co., Ltd., Shandong, with a molecular weight of approximately 300,000 and the polyurethane grade of WHT-1195

[0256] Examples 17 - 19

[0257] The difference between this example and Example 1 is that the molecular weight of the MQ silicone resin is different, as shown in Table 1.

[0258] Example 20

[0259] Using 100 g by mass of lithium nickel cobalt manganese oxide (LiNi x Co y Mn 1-x-y ​​​​(O2) is the raw material particles of the positive electrode active material, where x is 0.91 and y is 0.08. Dissolve 1 part by mass of methyl MQ silicone resin with an M / Q value of 0.75 and a molecular weight of 20,000 in 100 parts by mass of N-methylpyrrolidone, and stir at a speed of 1000 rpm for 30 min at 25 °C to obtain a uniform solution; then add 100 g of lithium nickel cobalt manganate powder, and stir at a speed of 2000 rpm for 60 min to obtain a uniform mixed system; filter to remove the excess solvent, and then dry the above-mentioned positive electrode active material particles loaded with MQ silicone resin in a vacuum oven at 105 °C for 24 h to obtain a solid mixture; grind the above-mentioned solid mixture to obtain the hydrophobic lithium iron phosphate positive electrode active material particles of Example 5 of the present invention. The structural formula of MQ silicone resin is [(CH3)3SiO 1 / 2 a [SiO 4 / 2 b , where a and b are positive integers respectively.

[0260] Example 21

[0261] Using 100 parts by mass of lithium nickel cobalt manganate (LiNi x Co y Mn 1-x-y O2) as the raw material particles of the positive electrode active material, where x is 0.91 and y is 0.08. Dissolve 1 part by mass of MQ silicone resin with an M / Q value of 0.75 and a molecular weight of 6000 and 0.01 part by mass of styrene-butadiene rubber from Beijing Zhonglai Chemical Co., Ltd. in 100 parts by mass of N-methylpyrrolidone, and stir at a speed of 1000 rpm for 30 min at 25 °C to obtain a uniform solution; then add 100 g of lithium nickel cobalt manganate powder, and stir at a speed of 2000 rpm for 60 min to obtain a uniform mixed system; filter to remove the excess solvent, and then dry the above-mentioned positive electrode active material particles loaded with MQ silicone resin in a vacuum oven at 105 °C for 24 h to obtain a solid mixture; grind the above-mentioned solid mixture to obtain the hydrophobic lithium iron phosphate positive electrode active material particles of Example 5 of the present invention. The structural formula of MQ silicone resin is [(CH2=CH)3SiO 1 / 2 a [SiO 4 / 2 b , where a and b are positive integers respectively.

[0262] Example 22

[0263] The difference between this example and Example 20 is that: the raw material particles of the positive electrode active material become lithium cobaltate (LiCoO2), and the molecular weight of MQ silicone resin is 6000. Other steps are the same as those in Example 20.

[0264] Example 23​​​​

[0265] The difference between this example and Example 22 is that the structural formula of the MQ silicone resin is [(CH2=CH)3SiO 1 / 2 a [SiO 4 / 2 b , the M / Q value of the added MQ silicone resin is 0.71, and the molecular weight is 6000. Other steps are the same as those in Example 22.

[0266] Example 24

[0267] The difference between this example and Example 23 is that the structural formula of the MQ silicone resin is [(CH3)2CH2=CHSiO 1 / 2 a [SiO 4 / 2 b The M / Q value of the added MQ silicone resin is 0.9. During the preparation process: 0.01 g of styrene-butadiene rubber from Beijing Zhonglai Chemical Co., Ltd. was dissolved in 100 g of N-methylpyrrolidone by mass. Other steps are the same as those in Example 23.

[0268] Comparative Example 1

[0269] The difference between this comparative example and Example 1 is that lithium iron phosphate (LiFePO4) positive electrode active material raw material particles are used as the positive electrode active material particles.

[0270] Comparative Example 2

[0271] The difference between this comparative example and Example 1 is that the lithium nickel cobalt manganese oxide positive electrode active material raw material particles in Example 16 are used as the positive electrode active material particles.

[0272] Comparative Example 3

[0273] The difference between this comparative example and Example 1 is that lithium cobalt oxide (LiCoO2) positive electrode active material raw material particles are used as the positive electrode active material particles.

[0274] Comparative Example 4

[0275] The difference between this comparative example and Example 1 is that the type of silicone resin in the coating layer is different, which is polydimethylsiloxane, and its structural formula is: (Si(CH3)2O)n, where n is a positive integer, and the weight-average molecular weight is 6000.

[0276] Test section

[0277] The positive electrode active material particles obtained in the examples and comparative examples were tested.

[0278] 1) Microscopic observation of positive electrode active material particles: ​​​​

[0279] 1. Sample preparation: Take a small amount of the positive electrode active material and paste it on the sample stage with conductive adhesive. Use tweezers to punch holes around the abnormal area for marking. Spray gold (platinum) on the bare film surface for 30 s and on the coated surface for 40 s, and observe using a scanning electron microscope (SEM).

[0280] 2. Parameter settings: Mode: In-lens, Voltage: 3 KV, Aperture: 30 μm, Working distance: 4.5 mm

[0281] 3. Test procedure: Take a photo of the entire abnormal position within the field of view, and take a set of photos with local magnification focused at a specific magnification.

[0282] Obtain Figure 4 the results. A is the micrograph of the unmodified lithium iron phosphate positive electrode active material raw material particles in Comparative Example 1. In the first row, the contents of Si, O, and P elements of the unmodified lithium iron phosphate positive electrode active material raw material particles in Comparative Example 1 are shown. Figure B is the lithium iron phosphate positive electrode active material particles prepared in Example 1. In the second row, the contents of Si, O, and P elements of the lithium iron phosphate positive electrode active material particles in Example 1 are shown. It shows that the surface of the positive electrode active material particles of the present application is coated with MQ silicone resin.

[0283] 2) Equilibrium water content test: Use the Karl Fischer coulometric method for water content test; Equipment: Micro moisture analyzer. After storing the lithium iron phosphate positive electrode active material particles in an environment of 60% humidity and 25 °C for 3 days, use the following method to detect the water content of the lithium iron phosphate positive electrode active material particles. Reference standard procedure: GB / T 11133-2015, specific test procedure: 1) Dry the lithium iron phosphate positive electrode active material particles in a vacuum oven at 105 °C for 72 h, and then let them stand at room temperature in a drying room for 72 h; 2) Bake the vial and rubber stopper at 85 °C for > 4 h; 3) Prepare samples in the drying room, weigh 0.6 g of the lithium iron phosphate positive electrode active material particles prepared in the example into a vial; 4) Seal with a sealing pliers, mark the sample mass (excluding the bottle) on the bottle body, and take an empty bottle sealed in the same environment as a blank sample for comparison; 5) Put the vial containing the sample into the automatic injection system of the equipment, heat the vial containing the sample and introduce dry gas during the test; 6) Purge the gas in the vial into the titration cup for absorption titration, and convert the result into the water content of the solid sample. Water content (μg / g): The mass of water contained in a unit mass of the sample, calculation formula: Water content = (sample moisture value - blank moisture value) / sample mass.

[0284] After testing, the water contents of the lithium iron phosphate positive electrode active material particles prepared in Example 1 and Comparative Example 1 in a sealed environment at a temperature of 25 °C and a humidity of 60% are as Figure 5 shown, indicating that the lithium iron phosphate positive electrode active material particles prepared in the examples of the present application have good hydrophobicity during storage and can also maintain a low water content during storage.

[0285]

Battery Performance Test

[0286] 1. DC Impedance Test of Battery

[0287] Taking Example 1 as an example, the process of DC impedance test of the battery is as follows: At 25°C, the battery corresponding to Example 1 is charged at a constant current of 1 / 3C to 4.3V, then charged at a constant voltage of 4.3V until the current is 0.05C. After standing for 5 minutes, the voltage V1 is recorded. Then, it is discharged at 1 / 3C for 30s, and the voltage V2 is recorded. Then, (V2 - V1) / 1 / 3C is used to obtain the internal resistance DCR1 of the battery after the first cycle. Repeat the above steps for the same battery, and at the same time record the internal resistance DCRn of the battery after the nth cycle (n = 1, 2, 3... 100). Taking the 100 point values of DCR1, DCR2, DCR3... DCR100 as the ordinate and the corresponding number of cycles as the abscissa, a curve graph of the battery discharge DCIR vs. the number of cycles corresponding to the modified lithium iron phosphate cathode active material particles of Example 1 is obtained.

[0288] During this test process, the first cycle corresponds to n = 1, the second cycle corresponds to n = 2,... the 100th cycle corresponds to n = 100. The battery internal resistance increase ratio of Example 1 in Table 1 = (DCRn - DCR1) / DCR1 * 100%. The test processes of Comparative Example 1 and other examples are the same as above. The data in Table 1 are the data measured after 100 cycles under the above test conditions.

[0289] 2. Detection of Battery Service Life: Taking Example 1 as an example, the battery cycle test process is as follows: The lithium-ion battery to be tested is placed in an environment of 60°C, charged at a constant current of 1 / 3C to 4.3V, maintained for 10 minutes, and then discharged at 0.5C to 2.5V. The capacity is tested and recorded; repeat the above steps for the same battery, and then perform charge and discharge cycles. After each cycle ends, record the capacity attenuation of the battery until the capacity attenuates to 80%, stop the test and calculate the cycle life of the battery. The internal resistance benchmarks of the positive electrode plates made of the cathode active material particles in Comparative Examples 1 - 3 are set to 100% respectively. The ratio of the internal resistance of the positive electrode plate made of the cathode active material particles of the example = the internal resistance of the positive electrode plate made of the cathode active material particles of the example / the internal resistance of the positive electrode plate made of the cathode active material particles in Comparative Examples 1 - 3. (The cathode active material particles of Examples 1 - 19 are compared with the cathode active material particles in Comparative Example 1 respectively, the cathode active material particles of Examples 20 - 21 are compared with the cathode active material particles in Comparative Example 2 respectively, and the cathode active material particles of Examples 22 - 24 are compared with the cathode active material particles in Comparative Example 3 respectively)

[0290] The performance of the positive electrode active material particles is shown in Table 1, and the battery performance including the positive electrode active material particles is shown in Table 1.

[0291] As can be seen from the test results in Table 1, the equilibrium water content of all modified positive electrode active materials in the implementation cases has significantly decreased, indicating that the method of coating with MQ resin can effectively improve the hydrophobic performance of the positive electrode active material. And preferably, the water content of the positive electrode active material coated with methyl silicone resin is relatively lower, indicating that the peripheral groups of methyl are more advantageous in improving the hydrophobic performance of the positive electrode active material particles.

[0292] The equilibrium water content of the unmodified lithium iron phosphate in Comparative Example 1 can be decreased from 1379 ppm to 655 ppm in Example 19 at the minimum. At the same time, the internal resistance of the example has slightly increased. The phenomenon of the increase in the internal resistance of the battery cell is normal because the uniformly coated silicone layer on the surface will inevitably hinder the migration of lithium ions kinetically, but its influence is small.

[0293] In other examples such as Examples 1-4, compared with Comparative Example 4, the polymer coating layer in Comparative Example 4 is polydimethylsiloxane, which can improve the hydrophobic performance of the positive electrode active material particles and reduce the equilibrium water content, but the internal resistance increases significantly to 193%, which greatly hinders the migration of lithium ions kinetically.

[0294] As can also be seen from the test results in Table 1, the battery service life of all positive electrode active materials with a polymer coating layer of MQ resin in the examples has been improved, indicating that MQ resin can improve the stability of the interface between the positive electrode active material particles and the electrolyte. For example, compared with Example 2, the battery service life in Example 19 has increased from 114% to 123%, indicating that higher molecular weight MQ resin is more advantageous in improving the interface stability. In addition, adding a small amount of binder also has a certain improvement on the interface stability, and the battery service life of Example 15 can be increased to 148%.

[0295] It should be noted that this application is not limited to the above embodiments. The above embodiments are only examples, and embodiments with the same structure in essence as the technical idea and the same function and effect within the technical solution scope of this application are all included in the technical scope of this application. In addition, within the scope of not departing from the main idea of this application, various deformations that can be thought of by those skilled in the art to the embodiments and other ways constructed by combining some constituent elements in the embodiments are also included in the scope of this application.

[0296]

[0297]

Claims

1. A positive electrode active material particle, characterized in that, The positive electrode active material particles have a polymer coating layer, wherein the polymer coating layer contains MQ silicone resin.

2. The positive electrode active material particles according to claim 1, characterized in that, The MQ silicone resin includes structural units represented by M and structural units represented by Q: Among them, O in the structural unit represented by M and the structural unit represented by Q 1 / 2 means that the oxygen atom is shared with another structural unit, and R1, R2, and R3 each independently represent hydrogen, C1-C5 alkenyl, haloalkyl, C3-C7 alkenoate group, phenyl, unsubstituted or substituted alkyl containing 1-6 carbon atoms, or alkylene oxide containing 2-4 carbon atoms; the substituents include any one of fluorine and chlorine elements.

3. The positive electrode active material particles according to claim 1 or 2, characterized in that, The MQ silicone resin satisfies at least one of the following conditions: 1) The weight average molecular weight of the MQ silicone resin is 4,000 to 20,000, optionally 5,000 to 10,000; 2) The molar ratio of the M structural unit to the Q structural unit in the MQ silicone resin is (0.5 to 1.2):1, optionally (0.7 to 0.9):1 3) The glass transition temperature of the MQ silicone resin is 40 to 200 °C.

4. The positive electrode active material particles according to any one of claims 1 to 3, characterized in that R1, R2, and R3 each independently represent any one of hydrogen, C1-C5 alkenyl, haloalkyl, C3-C7 alkenoate group, and phenyl; optionally, the C3-C7 alkenoate group includes an acrylate group; optionally, the acrylate group includes any one of methyl acrylate, ethyl acrylate, methyl 2-methylacrylate, and ethyl 2-methylacrylate; optionally, the haloalkyl includes any one of trifluoromethyl and chloromethyl.

5. The positive electrode active material particles according to any one of claims 1 to 4, characterized in that Based on the total mass of the positive electrode active material particles, the positive electrode active material particles include 0.01% to 5% by mass of the MQ silicone resin.

6. The positive electrode active material particles according to any one of claims 1 to 5, characterized in that, The positive electrode active material particles include a binder; optionally, based on the total mass of the positive electrode active material particles, the positive electrode active material particles include 0 to 2.5% of the binder; Optionally, the mass ratio of the binder to the MQ silicone resin is (0.01 to 0.5):1, optionally (0.1 to 0.5):

1.

7. The positive electrode active material particles according to claim 6, characterized in that, The binder includes one or more of an acrylic binder, a polyurethane binder, a silicone binder, a polyvinylidene fluoride binder, and an epoxy resin binder.

8. The positive electrode active material particles according to any one of claims 1 to 7, characterized in that, The average thickness of the polymer coating layer is 100 nm to 200 nm.

9. The positive electrode active material particles according to any one of claims 1 to 8, characterized in that, The positive electrode active material particles have a core-shell structure in which the coating layer coats the positive electrode active material core.

10. The positive electrode active material particles according to any one of claims 1 to 9, characterized in that, The positive electrode active material particles satisfy at least one of the following conditions: 1) The positive electrode active material particles include one or more of a layered metal oxide material, an olivine-type positive electrode material, and a spinel-type material; optionally, the olivine-type positive electrode material includes a lithium iron phosphate material; optionally, the positive electrode active material particles include one or more of a lithium nickel cobalt manganese oxide material and a lithium nickel cobalt aluminate material; 2) The average particle size Dv50 of the positive electrode active material particles is 0.52 μm to 4.1 μm, optionally 0.9 μm to 1.9 μm; 3) The specific surface area of the positive electrode active material particles is 7 m 2 / g to 15 m 2 / g, and can be optionally 10 m 2 / g to 13 m 2 / g.

11. A method for preparing a cathode active material particle having a polymer coating layer, characterized in that, The method includes: Providing a mixture containing positive electrode active material raw material particles, MQ silicone resin, and a solvent, optionally, the mass ratio of the MQ silicone resin to the positive electrode active material raw material particles is (0.01 to 5):100; Drying the mixture to form a polymer coating layer coating the positive electrode active material raw material particles.

12. A positive electrode sheet, characterized in that, It includes a positive current collector and a positive active material film layer disposed on at least one side of the positive current collector, and the positive active material film layer includes the positive active material particles described in any one of claims 1 to 10 or the positive active material particles prepared by the preparation method described in claim 11.

13. A battery cell, characterized in that, It includes the positive electrode tab described in claim 12.

14. A battery, characterized in that, It includes the battery cell described in claim 13.

15. An electrical device, characterized in that, It includes the battery described in claim 14.

Citation Information

Cited By

  • Coated modified positive electrode material suitable for solid-state battery, preparation method of coated modified positive electrode material and solid-state battery

    CN121172100A